The Effectiveness of MEA Cooperative Learning Model by Scientific Approach to Improve Students' Mathematics Learning Outcomes - Sartia Sartia; Andi Mariani Ramlan; Made Subawo (Universitas Sembilanbelas November Kolaka, 2021)
The objectives of this study include: 1) to determine the mathematics learning outcomes of students in class X.IPS SMAN 2 Mawasangka Tengah before the MEA cooperative learning model with a scientific approach is applied; 2) to find out the average increase in students' mathematics learning outcomes after applying the MEA cooperative learning model with a scientific approach; 3) to find out the MEA cooperative learning model with a scientific approach is effectively applied in improving students' mathematics learning outcomes. This type of research is Pre-Experimental with One-Group Pretest-Posttest Design. The population in this study were all students of class X.IPS SMAN 2 Mawasangka Middle School Year 2020/2021 with a total of 27 students, while the sample in this study was the entire population selected using the totally sampling technique. Data on students' mathematics learning outcomes were obtained from the results of the Pretest and Posttest in the form of essays, indicating that there was an average increase in students' mathematics learning outcomes before being applied (60.95%) and (75.17%) after the MEA learning model was applied. Furthermore, the results of testing based on hypothesis testing were carried out with one sample t-test statistic (one sample t-test) obtained , then it was rejected and accepted. So it was concluded that the MEA cooperative learning model was effective in improving students' mathematics learning outcomes.